Pengaruh Metode Amtsilati Terhadap Keterampilan Membaca Kitab Kuning - Ely Fadilah (Institut Agama Islam Darusssalam Blokagung, 2022)
This research purpose to determine the effect and how much influence the amtsilati method has on the reading skills of the yellow book of amtsilati guidance participants at the Darussalam Putri Selatan Islamic Boarding School in 2020-2021. This study uses quantitative methods. Data were collected using a questionnaire technique with 48 students participating in Amtsilati guidance as respondents. Hypotheses were formulated and tested using simple regression analysis. After analyzing the data collected, it was found that (1) There was a significant influence of the Amtsilati method on reading skills of the yellow book. Based on the results of the T test, it can be seen that tcount > ttable i.e. 8,953 > 2,013, which means Ho is rejected and Ha is accepted; (2) the percentage of R Square value is 0.635, which means that the amtsilati method (X) has a major influence on reading skills of the yellow book (Y) of 63.5% and the remaining 36.5% is influenced by other variables.